10.7k views
5 votes
What is the value of the product (3 – 2i)(3 + 2i)?

User Fai Ng
by
5.1k points

2 Answers

3 votes

Answer:

13.

Explanation:

(3 - 2i)(3 + 2i)

= (3 * 3) + (-2i * 3) + (2i * 3) + (-2i * 2i)

= 9 - 6i + 6i - 4
√(-1) ^(2)

= 9 - 4(-1)

= 9 + 4

= 13

Hope this helps!

User Fabis
by
5.3k points
3 votes

Answer:

13

Explanation:

(3 - 2i)(3 + 2i)

Expand

(9 + 6i - 6i - 4i^2)

Add

(9 - 4i^2)

Convert i^2

i^2 = (
√(-1))^2 = -1

(9 - 4(-1))

Add

(9 + 4)

= 13

User Jonas Kongslund
by
5.6k points